Sensory profiles of artisanal smoked dry-cured ham as affected by production season - Ivica Kos (Journal of Central European Agriculture, 2019)
The aim of this paper was to determine the effect of production season on sensory attributes of artisanal smoked dry-cured ham and to elaborate findings by non-parametric testing and principal component analysis. Artisanal drycured hams (73 samples) were collected on open market during five consecutive production seasons from the year 2011 to 2015, and quantitative descriptive analysis was performed. The results showed that 10 out of 18 sensory attributes were significantly different (P<0.05) between production seasons. Principal component analysis revealed that the first two principal components explained 45.53% of the total variance. It was found that the odor intensity and after-taste had the strongest positive correlations with the overall acceptability, whereas rancid flavor, mold aroma, bitterness and sourness had the strongest negative correlations. There was no clear separation of production seasons, and a lot of overlapping was observed because dry-cured hams within every production season originated from 12 to 18 individual producers on open market which raised product variability. However, it was possible to describe the seasonal pattern of every production season with specific sensory profile. It can be concluded that production season is a useful variable for describing changes of sensory traits in artisanal dry-cured ham manufacture.